Correlation Study of Students’ Scientific Argumentation, Critical Thinking, and Concept Mastery on Newton’s Law of Motion (Universitas Negeri Surabaya, 2020)
Considering the importance of each competency to the students’ development then those they should have a positive correlation with each other. Therefore, this research aims to find the relation between argumentation skill, critical thinking, and concept mastery of Senior High School Students and to find their level of scientific argumentation, critical thinking, and concept mastery ability. The research used mixed-method. The qualitative data was focused on students’ scientific argumentation while the quantitative data was focused on the level of variables based on the indicator, correlations between variables, and the number of students in each level of each variable. The participant in this research is senior high school students who already learned Newton’s Law of motion. The critical thinking skill and concept mastery test included some different multiple-choice problems and followed by an essay of reason/ support for the answer each. While, the argumentation test formed by chained questions, including multiple choice test and essay test to figure out the Toulmin Argumentation Pattern (TAP). The test was given without giving any treatment for the participant. Based on the result concluded that: There is a very strong positive correlation between scientific argumentation, critical thinking skill, and concept mastery; While their scientific argumentation ability categorized intermediate, students’ have a low grade of critical thinking skill and concept mastery. Keywords: scientific argumentation, critical thinking skill, concept mastery